Unusual presentation of immunoglobulin A vasculitis with acute scrotal swelling and epididymo orchitis in a 5-year-old boy - Putcha, Sahithi; Katakamsetty, Maheswari (International Journal of Contemporary Pediatrics, 2025)
Immunoglobulin A (IgA) vasculitis, formerly known as Henoch-Schönlein purpura (HSP), is a small vessel vasculitis primarily affecting children. It commonly presents with palpable purpura, arthralgia, abdominal pain, and renal involvement. However, atypical presentations can occur, posing diagnostic challenges. Here, we present a case of IgA vasculitis in a 5-year-old boy with a unique manifestation of epididymitis as the primary presenting symptom. Scrotal ultrasound demonstrated Epididymo-orchitis with funiculitis. Skin examination revealed scattered palpable purpura over the lower extremities. Thus, a clinical diagnosis of IgA Vasculitis is made. The patient recovered with corticosteroids and supportive care.